(untitled) (Research, Society and Development, 2020)
This paper presents the concept of the collective unconscious postulated by Dr. Carl Gustav Jung and some concepts of contemporary physics that culminated with the idea of elaborating a Theory of Everything (ToE). It intends to start a discussion about the similarity of these concepts and proposes the continuation of the discussion aiming at a better theoretical clarification of the subject and the possibility of including experiments for empirical verification. This article was elaborated from bibliographic consultation and information transmitted in the Latu Sense postgraduate course in analytical psychology at Santa Ursula University.